Epidemiology of ovarian cancer in Thailand : Pilot study from Khon Kaen Population –based cancer registry + - Titapant, Vitaya; Pengsaa, Prasit; Vatanasapt, Vanchai (Srinagarind Medical Journal, 2013)
The study was carried out to determine the accurate incidence and magnitude of problems of ovarian cancer in khon Kaen province and also to act as a pilot study for the feaxsibility of conducting the population-based registry of all ovarian cancer cases in Thailand. Under the method of population – based cancer registry , every case of ovarian cancer diagnosed from every health service center in KhonKaen province during the period from January 1,1985 to December 31 , 1987 was collected by the cancer unit , Faculty of Medicine , Khonkaed University both in passive and active methods After carefull check by unit’s staffs and computerized system , the cases were record in computer for further study. There were totally 72 new cases of ovarian cancer collected in this three-year period. The crude incidence rates varied from 3.06 to 3.37 per 100,000 poputation per year while the agestandardized incidence rates compared to standard world population varied from 4.15 to 4.55 per 100,000 population per year. The death cases of this disease in the same period of time were totally 20 with the crude mortality rates varied from 0.64 to 1.30 per 100,000 population per year while the age-standardized mortality rates varied from 0.81 to 1.94 per 100,000 population per year. The result of this study reveals the more reliable statistics about incidence and mortality rates of ovarian cancer than it has previously been reported. It showed the rather low incidence when compared with other countries in the world and still not the major cause of death in KhonKaen female population.